Approximating Non Linear Higher Order ODEs By A Three Point Block Algorithm - Nurullah Rasedee, Ahmad Fadly; Abdul Sathar, Mohammad Hasan; Othman, Khairil Iskandar; Hamzah, Siti Raihana; Ishak, Norizarina (Plos, 2024)
Indexed by WOS/SCOPUS/ERA